An alternative philosophy of development - Mathur, B P (Routledge, 2017)
About the Book: An Alternative Philosophy of Development: From Economism to Human Well being While development has been the foremost agenda before successive governments in India, it has been viewed narrowly — from the perspective of economic development and particularly in terms of Gross Domestic Product (GDP). This book questions such an approach. It breaks from the conventional wisdom of GDP growth as being a definitive measure of success of a countrys policies and offers an alternative development philosophy. The book underlines that in a successful model of development, the countrys economic policies will have to synergize with its cultural ethos and that the objective of development